Prevedba ocen kakovosti stoječih dreves na izbranih objektih v sortimentno strukturo - Krajnc, Luka (Acta silvae et ligni, 2025)
A method for converting stem quality assessments into log grade structure was presented. For 123 trees of four species, a comparison was made between actual assortments after felling and virtual assortments based on pre-harvest quality estimates. A total of 869 actual assortments were measured, and the results were compared with virtual bucking and sorting into log grades. The results showed good agreement for spruce, while the accuracy for hardwoods was lower due to undetectable internal defects. The method proved useful for improving harvest planning and assessing forest stand quality. Further refinement of existing models (e.g., knot size) would increase the the accuracy and applicability of the approach under Slovenian conditions.
Keywords: assortment; conifers; forest timber assortments; gozdni lesni sortimenti; grče; hardwoods; iglavci; internal wood defects; knots; listavci; notranje napake lesa; ocena kakovosti; prostorninska struktura; quality assessment; računsko krojenje; sortimentacija; standing trees; stoječa drevesa; virtual bucking; volume structure